Strategies of Social Studies Teachers in Using Natural Tourist Attractions as Learning Resources for Middle School Students in Semarang Regency - Apik Budi Santoso; Pradika Adi Wijayanto; Ferani Mulianingsih; Iwan Saputra; Andhika Rizqy Heristama (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
. Education generally demands that the learning process should not be directed solely toward textual understanding, but rather encourages contextual learning. In this approach, learning should utilize a variety of learning resources that keep pace with advancements in science and technology, and are also closely tied to up-to-date developments in the surrounding environment and society. By using local environmental issues as a learning resource, it is expected that students will obtain more accurate and reliable information. The aim of this research activity is to identify and explain natural tourist attractions in Semarang Regency as learning resources for social studies in junior high schools. The method used is qualitative. The data sources consist of primary and secondary data. Data collection techniques include interviews, observation, and document/archive analysis, while the validity of the data is ensured through technique triangulation.